1999
DOI: 10.1111/j.1751-1097.1999.tb08138.x
|View full text |Cite
|
Sign up to set email alerts
|

Laser Flash Photolysis Studies of the UVA Sunscreen Mexoryl SX

Abstract: The results of a nanosecond laser flash photolysis investigation of the UVA sunscreen Mexoryl-SX in various solvent environments and within a commercial sunscreen formulation are reported. To the best of our knowledge this is the first laser flash photolysis study of a commercial suncare formulation. In each of these environments kinetic UV-visible absorption measurements following nanosecond 355 nm laser excitation reveals a short-lived species with a solvent-dependent absorption maximum around 470-500 nm and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(38 citation statements)
references
References 11 publications
(6 reference statements)
1
37
0
Order By: Relevance
“…This method is available if the triplet-triplet absorption spectrum of the triplet-energy donor is known. Unfortunately, the photochemistry of BMDBM is complex [32,33]. To the best of our knowledge, the triplet-triplet absorption spectrum of BMDBM (enol form) has not been reported.…”
Section: Introductionmentioning
confidence: 89%
“…This method is available if the triplet-triplet absorption spectrum of the triplet-energy donor is known. Unfortunately, the photochemistry of BMDBM is complex [32,33]. To the best of our knowledge, the triplet-triplet absorption spectrum of BMDBM (enol form) has not been reported.…”
Section: Introductionmentioning
confidence: 89%
“…49 Photophysical studies on di-substituted 1,3-diphenyl-1,3propanedione compounds have shown that MeCN supports very slow exchange between tautomeric states, whereas protic solvents, including MeCN-water mixtures, enhance rates signicantly. 50,51 Water is oen used as a solvent or co-solvent in uorination reactions to aid solubility of Selectuor™. 28 Our studies show that the solubility limit of Selectuor™ in water is $500 mM, compared to $50 mM in MeCN.…”
Section: Kinetics Of Keto-enol Tautomerism In Compounds 4a-dmentioning
confidence: 99%
“…The relative yields of these various non-H-bonded forms, and the rates with which they relax to the starting S 0 (H-bonded) state are sensitive to the choice of solvent. 206,207 As in so many of these examples, complete ground state recovery is not observed, implying some (low) probability for forming a long-lived photoproduct, possibly a stable keto-AB isomer. 207,208 …”
mentioning
confidence: 99%
“…14 shows, its lowest energy tautomer lacks an OH group. Nonetheless, AB tends to exist in a H-bonded enol form (characterised by an intramolecular H-bond), 206 and the most detailed current picture regarding its excited state photophysics stems from transient absorption studies of AB in cyclohexane, acetonitrile and methanol by Crim and coworkers. 207 The excited H-bonded enol form (termed a chelated enol in the original work) 207 of AB formed by absorption of a 350 nm photon is deduced to decay on a sub-ps timescale, yielding several different non-H-bonded (or non-chelated) enols.…”
mentioning
confidence: 99%